Substrate–Enzyme Interactions in Intramembrane Proteolysis: γ-Secretase as the Prototype - Liu, Xinyue; Zhao, Jing; Zhang, Yingkai; Ubarretxena-Belandia, Iban; Forth, Scott; Lieberman, Raquel L.; Wang, Chunyu (Frontiers in Molecular Neuroscience, 2020)
Intramembrane-cleaving proteases (I-CLiPs) catalyze the hydrolysis of peptide bonds within the transmembrane regions of membrane protein substrates, thus releasing bioactive fragments that play critical roles in many physiological and pathological processes. Based on their catalytic mechanism I-CLiPs can be divided on metallo, serine, aspartyl and glutamyl proteases. Presenilin is the most prominent among I-CLiPs, as the catalytic subunit of γ-secretase complex responsible for cleaving the amyloid precursor protein (APP) and Notch, among many other membrane substrates. Cryo-electron microscopy structures of γ-secretase revealed that TM2 and TM6 of presenilin are highly dynamic. γ-secretase binding unwinds the substrate transmembrane helix from the C-terminus, resulting in an intermolecular β-sheet between the presenilin and the substrates APP and Notch distal to the initial -cleavage site. Despite astounding progress in recent years, many crucial questions remain unanswered regarding the mechanism of -secretase. These include how the enzyme recognizes and recruits substrates, how substrates are translocated from an initial docking site to the active site, how active site aspartates recruit and coordinate catalytic water, and the nature of the mechanisms of processive trimming of the substrate and product release. Answering these questions will have important implications for drug discovery aimed at selectively reducing the amyloid load in Alzheimer’s disease with minimal side effects.